2017
DOI: 10.1007/s10680-016-9407-z
|View full text |Cite
|
Sign up to set email alerts
|

The Reversed Gender Gap in Education and Assortative Mating in Europe

Abstract: While in the past men received more education than women, the gender gap in education has turned around: in recent years, more highly educated women than highly educated men are reaching the reproductive ages. Using data from the European Social Survey (rounds 1-6), we investigate the implications of this reversed gender gap for educational assortative mating. We fit multilevel multinomial regression models to predict the proportions of men and women living with a partner of a given level of education, conting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 49 publications
5
96
1
9
Order By: Relevance
“…Our focus here is on assortative mating by education, because education may affect individual economic potential, as well as individual tastes, preferences, and lifestyles (Blossfeld 2009). While educational homogamy remains the most common mating pattern in Europe (Blossfeld and Timm 2003;Hamplova 2009;De Hauw et al 2017), marked changes in heterogamous couples have occurred. Recent studies have shown that unions in which the man is more educated than the woman (hypergamy) are now less common than unions in which the woman is more educated than the man (hypogamy) (Esteve et al 2012;Grow and Van Bavel 2015;De Hauw et al 2017).…”
Section: Non-marital Family Formation and The Role Of Educational Assmentioning
confidence: 99%
“…Our focus here is on assortative mating by education, because education may affect individual economic potential, as well as individual tastes, preferences, and lifestyles (Blossfeld 2009). While educational homogamy remains the most common mating pattern in Europe (Blossfeld and Timm 2003;Hamplova 2009;De Hauw et al 2017), marked changes in heterogamous couples have occurred. Recent studies have shown that unions in which the man is more educated than the woman (hypergamy) are now less common than unions in which the woman is more educated than the man (hypogamy) (Esteve et al 2012;Grow and Van Bavel 2015;De Hauw et al 2017).…”
Section: Non-marital Family Formation and The Role Of Educational Assmentioning
confidence: 99%
“…As access to education becomes more prevalent for men and women—in tandem or at different paces—intramarital differences in educational status also change. Substantial research from various geographic contexts (Blossfeld, ; De Hauw et al, ; Esteve, García‐Román, & Permanyer, ; Esteve et al, ; Mare, ; Schwartz & Mare, ; Smits & Park, ; Smits, Ultee, & Lammers, ) has provided insight into, for example, the increasingly similar education of wives and husbands in the United States (Mare, ) and the withdrawal from marriage among highly educated women in Japan (Raymo & Iwasawa, ). We extend this research into sub‐Saharan Africa, a context characterized by unusual heterogeneity in educational trends, encompassing contexts where attending secondary school has long been typical and contexts where attending any school at all remains exceptional (Frye & Lopus, ).…”
Section: Educational Expansion and The Prevalence Of Hypergamy Hypogmentioning
confidence: 99%
“…Educational characteristics influence a wide range of demographic phenomena, including whether, when, and whom we marry. In settings where cultural norms dictate a distaste for pairings between lower status men and higher status women, a person's years of schooling will influence the likelihood or necessity of such a match (De Hauw, Grow, & Van Bavel, 2017;Raymo & Iwasawa, 2005). At the household level, intramarital status differentials influence household decision making (Pyke & Adams, 2010), family planning (Behrman, 2016), and intimate partner violence (Behrman, 2018;Jewkes, 2002).…”
mentioning
confidence: 99%
“…First, the distribution of educational attainment has become more equal for women and men in many countries (OECD, ). In fact, in Germany, more women than men attain an educational level that entitles them to tertiary education (“Abitur” and “Fachabitur”) (Helbig, ; see De Hauw, Grow, & Van Bavel, , Esteve et al, , van Bavel, for further consequences of the reversed gender gap in education). Second, men and women of equal educational attainment share selective educational meeting contexts for a longer time (Blossfeld, ).…”
Section: The Theoretical Concept Of the Partner Marketmentioning
confidence: 99%